MODERATING ENTREPRENEURIAL MINDSET: THE INFLUENCE OF PRODUCT SPECIFICATIONS, ONLINE CUSTOMER REVIEWS AND RATINGS, AND SALES PROMOTIONS ON PURCHASING DECISIONS OF SUSTAINABLE FASHION IN THE SHOPEE MARKETPLACE - Aljihan, Safira Afifa; Hermeindito (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study aims to investigate the moderating effect of entrepreneurial mindset on the purchasing decisions of sustainable fashion products in the Shopee marketplace, focusing on product specifications, online customer reviews and ratings, and sales promotions as independent variables. In the context of the rapidly developing fashion industry, consumers are showing a high interest in products that are not only aesthetically appealing but also sustainable. This research employs a quantitative approach and involves participation from consumers who have made purchases of sustainable fashion products on Shopee. Data were collected through an online questionnaire that encompasses aspects of product specifications, online customer reviews and ratings, sales promotions, and entrepreneurial mindset. The results indicate that product specifications, online customer reviews, and sales promotions significantly influence purchasing decisions, while the entrepreneurial mindset does not appear to moderate the relationship between these variables and purchasing decisions. These findings provide important insights for business practitioners in designing effective and sustainable marketing strategies, as well as highlighting the significance of consumer understanding of sustainability values in their purchasing decision-making.